Hubungan Karakteristik Responden Dengan Pelaksanaan Pencegahan Infeksi Nifas di RS Charis Medika Batam Tahun 2023 - Erdayani Surbakti; Dewi Sartika Hutabarat; Fertika Fariana Sianipar; Oktavania Oktavania; Syahrin sakinah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Nifas infections that attack the breast or the mastitis are caused by bacterial contamination when nipple abrasions. Infections in the lungs can occur in mothers who receive general anesthesia. Phlebitis caused by contaminated syringes. Cleanliness of body, clothing, bed, and environment are vital to maintaining. Admission of hygiene would have prevented germs in nifas' mother's body. When a mother bathes it is recommended to wash all the bodies as far as perineum with soap. The midwife was instrumental in providing support during the nifas days. The research design used in this study is a correlative descriptive research design with a cross sectional approach which aims to determine the relationship between the characteristics of respondents and the implementation of postpartum infection prevention at Charis Medika Hospital, Batam in 2023. From the research results, the characteristics of the respondents were asked about in this study. namely age, education and work experience. Descriptive data on the ages of respondents obtained that the lowest age was 22 years and the highest age was 56 years. Data collection in this research starts from April to June 2023.